Pathogenic PTPN11 variants involving the poly‐glutamine Gln255‐Gln256‐Gln257 stretch highlight the relevance of helix B in SHP2's functional regulation. Issue 6 (11th March 2020) - Martinelli, Simone; Pannone, Luca; Lissewski, Christina; Brinkmann, Julia; Flex, Elisabetta; Schanze, Denny; Calligari, Paolo; Anselmi, Massimiliano; Pantaleoni, Francesca; Canale, Viviana Claudia; Radio, Francesca Clementina; Ioannides, Adonis; et al.
Abstract: Germline PTPN11 mutations cause Noonan syndrome (NS), the most common disorder among RASopathies. PTPN11 encodes SHP2, a protein tyrosine‐phosphatase controlling signaling through the RAS‐MAPK and PI3K‐AKT pathways. Generally, NS‐causing PTPN11 mutations are missense changes destabilizing the inactive conformation of the protein or enhancing its binding to signaling partners. Here, we report on two PTPN11 variants resulting in the deletion or duplication of one of three adjacent glutamine residues (Gln 255 ‐to‐Gln 257 ). While p.(Gln257dup) caused a typical NS phenotype in carriers of a first family, p.(Gln257del) had incomplete penetrance in a second family. Missense mutations involving Gln 256 had previously been reported in NS. This poly‐glutamine stretch is located on helix B of the PTP domain, a region involved in stabilizing SHP2 in its autoinhibited state. Molecular dynamics simulations predicted that changes affecting this motif perturb the SHP2's catalytically inactive conformation and/or substrate recognition. Biochemical data showed that duplication and deletion of Gln 257 variably enhance SHP2's catalytic activity, while missense changes involving Gln 256 affect substrate specificity. Expression of mutants in HEK293T cells documented their activating role on MAPK signaling, uncoupling catalytic activity and modulation of intracellular signaling. These findings further document the relevance of helix B in the regulation of SHP2's function. Abstract : Rare PTPN11 variants resulting in the deletion or duplication of one residue within the 255‐257 poly‐glutamine stretch of SHP2 cause Noonan syndrome The helix B of SHP2 has a crucial role in the functional regulation of the phosphatase Enhanced catalytic activity in vitro is not necessarily required for SHP2's mutants causing Noonan syndrome Increased phosphatase activity does not necessarily imply a disease‐causing role for the relative PTPN11 variant.